Pandangan Al-Ghazali Mengenai Peranan Akal dalam Pendidikan dan Implementasinya dalam Brain Based Learning - Lismawati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
This research is motivated because learning methods are still often used that are still overriding and have not optimized brain function or reason which is essentially very helpful in the learning process. Learning that sometimes makes sense and the brain is difficult to accept makes the learning process inefficient. The levels of each human brain are also different which requires students to learn how the brain works well, so that it can be applied as a learning method. Al-Ghazali is one of several figures who express his opinion about reason and science in education. The role of reason and its function can then be implemented into a learning method or method called Brain Based Learning. This type of research is library research, in which the data taken for this research is extracted from books and other literature. The results of this study that the function and role of the mind or brain that exist in humans that are influential in the world of science (education) discussed by Al-Ghazali shows a method that is very helpful in the learning process is by optimizing brain functions and work as is done in Brain Based Learning.